Taraxacum assemanii represents a new section: A revision of the misinterpreted Taraxacum primigenium, and the elucidation of the enigmatic Taraxacum section Primigenia (Compositae, Crepidinae) - Kirschner, Jan; Štěpánek, Jan; Doostmohammadi, Moslem; Zeisek, Vojtěch (Phytotaxa, 2021)
On the basis of new gatherings at the type locality, Taraxacum primigenium was evaluated taxonomically. Its achenes differ substantially from the protologue description that is based on achenes of T. assemanii. Taraxacum primigenium, also on the basis of an nrDNA analysis, is close to T. sect. Piesis, and represents a narrow endemic confined to the Lalezar Mts., SE Iran. Taraxacum assemanii, newly typified, is known from mountains of SE Anatolia and Lebanon, and from the Zagros in SW Iran. It is characterized by large, almost or totally smooth achenes with indistinct cone and a very gradual achene body/beak transition, a thick short beak and a short, slightly brownish pappus. It represents a single member of a newly described section, T. sect. Pristina. The name of T. sect. Primigenia, although with a diagnosis corresponding to the characters of T. assemanii, is to be interpreted according to its type, T. primigenium, and is understood as a synonym of T. sect. Piesis. Another taxon evaluated, T. cylleneum, endemic to several mountain ranges in of Peloponnesos, Greece, is similar to T. primigenium, and very close to the core taxa of T. sect. Piesis. All the species dealt with reproduce sexually.